Implikasi Yuridis Kontrak Mitra (Disguised Employment) Terhadap Hak Jaminan Sosial Ketenagakerjaan Tenaga Medis dan Tenaga Kesehatan - Mahesa Paranadipa Maykel; Fahmi Hakam (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2025)
Changes in the employment structure in Indonesian healthcare facilities (Fasyankes) over the past decade have shown a significant increase in the use of partner contracts, outsourcing, and independent cooperation agreements for medical and health workers. This employment relationship pattern is considered administratively flexible, but this unclear status is an attempt by Fasyankes to avoid legal obligations (avoidance of liability), particularly the obligation to fulfill the right to protection of Employment Social Security as guaranteed in Law No. 24 of 2011 concerning BPJS, and Law No. 13 of 2003 concerning Manpower as amended by Law No. 06 of 2023 on Job Creation. This article aims to analyze the legal implications of the use of partner contracts on the fulfillment of BPJS Employment membership rights for healthcare workers, identify regulatory and implementation gaps, and formulate policy recommendations to ensure the fulfillment of social protection rights in accordance with national legal standards and global health employment practices. The research method used a literature review approach, with a Statute Approach and a Conceptual Approach (the principle of Substance over Form), utilizing analysis of laws and regulations, policy documents, and case studies of employment law in the health sector in Indonesia. The analysis shows that "partner" status does not eliminate the obligation of healthcare providers to provide social security protection. Many healthcare provider partner contracts are essentially disguised employment relationships (wage earners), requiring healthcare facilities to cover the BPJS Employment program. However, weak law enforcement, unclear employment status, and minimal employment contract literacy mean that many healthcare workers lose their basic rights to protection from work risks, occupational accidents, and old-age security. This study concludes that regulatory harmonization, standardization of healthcare worker employment contracts, and optimization of oversight are needed to ensure healthcare workers' rights are met as mandated by the national social security system and to prevent disguised employment. Keywords: Social Security, Medical Personnel, Healthcare Personnel, Partner Contracts, BPJS Employment